Applications of non‐stationary thermal wave imaging methods for characterisation of fibre‐reinforced plastic materials. Issue 2 (1st January 2013) - Mulaveesala, R.; Ghali, V. S.; Arora, V.
Abstract : The active thermal nondestructive testing and evaluation method is a rapidly growing testing procedure for a quick and remote inspection procedure for fibre‐reinforced plastics. Conventional modulated lock‐in thermography significantly contributed to this field by allowing usage of low peak power controlled stimulations followed by phase based detail extraction procedures. But demand of repetitive experimentation required for depth scanning of the test object limits its applicability for realistic critical applications and demands multi‐frequency low power stimulations for better resolution and sensitivity for sub‐surface defect detection. Frequency modulated thermal wave imaging and coded excitation thermal wave imaging methods permitting multi‐frequency stimulations cater for these needs and facilitate depth scanning of the test object in a single experimentation cycle. Recently introduced three‐dimensional pulse compression is an alternative to phase based analysis for these stimulations by providing enhanced defect detection even in noisy environmental and experimental conditions. Defect detection capability and sizing by these non‐stationary thermal wave imaging methods are highlighted using the pulse compression approach. The present experimental study has been carried out on a carbon fibre reinforced plastic specimen with flat bottom holes.